A Framework to Foster Oral Health Literacy and Oral/General Health Integration - Kleinman, Dushanka V.; Horowitz, Alice M.; Atchison, Kathryn A. (Frontiers in Dental Medicine, 2021)
Abstract Science and technology advances have led to remarkable progress in understanding, managing and preventing disease and promoting human health, creating new challenges for health literacy and the integration of oral and general health. We adapted the 2004 Institute of Medicine health literacy framework to highlight the intimate connection between oral health literacy and the successful integration of oral and general health and to recognize the roles of culture and society, educational systems and health systems as overlapping intervention points for effecting change We believe personal and organizational health literacy have the power to meet the challenges of an ever- evolving society and environment, and are essential to achieving oral and general health integration. The new “Oral Health Literacy and Health Integration Framework” recognizes the complexity of efforts needed to achieve an equitable health system that includes oral health, while acknowledging the critical partnership of health literacy and integration. The Framework was designed to stimulate systems-thinking and systems-oriented approaches. Its interconnected structure is intended to inspire discussion, drive policy and practice actions and guide research and intervention development.